Assessment of combining ability for grain yield of self-pollinated S5 maize (Zea mays L.) families of mixed germplasm - О. Л. Гайдаш (Plant Varieties Studying and Protection)
Purpose. Assessment and selection of self-pollinated S5 maize (Zea mays L.) families with high combining ability and wide adaptive capacity obtained on the basis of specially produced hybrids by crossing elite lines of various genetic plasms with the best main agronomic characters. Methods. Field studies, mathematico-statistical evaluation. Results. An amplitude of grain yield ranging from 5.96–10.96 t/ha (x = 8.44 t/ha) in 2013 to 2.67–7.59 t/ha (x = 5.08 t/ha) in 2014 was determined in the course of study of the testcrosses of self-pollinated S5 families. It was found that different response of genotypes of the studied testcrosses to the year conditions significantly affected the average yield level, which decreased in the stressful 2014 by 3.4 t/ha as compared to 2013. The results of the assessment based on the general and specific combining ability of new parent material of mixed germplasm were shown. A significant variability of the estimates of GCA (general combining ability) effects depending on the year conditions was observed in the course of study. A marked difference in the estimates of GCA effects based on the grain yield was revealed. They were persistently high in 19% of the best self-pollinated families in both years, 14% of the families had persistently low estimates of GCA effects, 67% changed their value depending on the genotype and year conditions. Conclusions. 17 best self-pollinated families with persistently high estimates of GCA, 6 families featuring high tolerance to drought and 4 families with persistently high variances of SCA were selected. The selected families will be used as a parent material in selection programs aimed to create new high performance hybrids.